2008
DOI: 10.1002/cbic.200800188
|View full text |Cite
|
Sign up to set email alerts
|

Biotinylated Bi‐ and Tetra‐antennary Glycoconjugates for Escherichia coli Detection

Abstract: Glycans cover the surface of all mammalian cells. Several toxins and pathogens use these glycans to bind and infect the cell. Using a versatile modular synthetic strategy, we have developed biotinylated bi- and tetraantennary glycoconjugates to capture and detect E. coli and compared the capturing ability of these molecules to commercial polyclonal antibodies. Magnetic beads were coated with biotinylated glycoconjugate or antibody, and these beads were used to capture, isolate, and quantify bacterial recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…By using our previously described synthetic strategy, which has been successfully used to develop ligands for the capture of toxins, [10] viruses [11] and bacteria, [12] we constructed a panel of biotinylated S-sialosides that could adopt a variety of topologies ( Figure 1). The biotinylated S-sialosides, unlike naturally occurring O-sialosides, are impervious to cleavage by viral neuraminidase (NA) and therefore, can be used to analyze HA, NA, and intact virus.…”
mentioning
confidence: 99%
“…By using our previously described synthetic strategy, which has been successfully used to develop ligands for the capture of toxins, [10] viruses [11] and bacteria, [12] we constructed a panel of biotinylated S-sialosides that could adopt a variety of topologies ( Figure 1). The biotinylated S-sialosides, unlike naturally occurring O-sialosides, are impervious to cleavage by viral neuraminidase (NA) and therefore, can be used to analyze HA, NA, and intact virus.…”
mentioning
confidence: 99%
“…In this sense, MNPs have the unique advantage than the bacteria attached to the glycoMNPs can be separated from the unbound ones just with a magnet. Pioneering work of El-Boubbou et al [66] and Hatch et al [67] demonstrated that MNPs functionalized with glycoconjugates could be used to isolate and quantify Escherichia coli, reaching higher sensitivity and selectivity than the same MNPs functionalized with antibodies [67]. Since then, some other examples where glycoMNPs are used to detect bacteria can be found in the literature [68].…”
Section: Pathogen and Cell Isolationmentioning
confidence: 96%
“…decontamination. In a related study, much larger (2.8 μm diameter) magnetic particles 16 conjugated via a streptavidin monolayer were incubated with a mannose derivative linked to biotin (Hatch et al, 2008). The resulting particles were also used to detect E. coli.…”
Section: Detectionmentioning
confidence: 99%